Healthy Pregnancy Preparation with Nutritional Fulfillment The Balanced One - Irnawati Irnawati; Uliarta Marbun (Jurnal Pengabdian Masyarakat Edukasi Indonesia, 2025)
Adolescents often face challenges in understanding and maintaining their reproductive health due to limited access to accurate information and appropriate guidance. This community service project aims to enhance adolescents’ self-efficacy in maintaining reproductive health through structured reproductive health education. The program was implemented in collaboration with local schools and involved interactive sessions, discussions, and educational media tailored to the developmental needs of adolescents. The results showed a significant improvement in participants’ knowledge, attitudes, and confidence in making informed decisions related to their reproductive health. This activity highlights the importance of early, comprehensive, and culturally sensitive health education as a preventive strategy to promote healthier adolescent development. It also emphasizes the role of community involvement in empowering youth to take responsibility for their well-being